OPTIMALISASI ETOS KERJA GURU SMK JAKARTA BARAT MELALUI BUDAYA ORGANISASI DAN KECERDASAN EMOSIONAL - Fitri, Euis Nessia; Hakim, Dani Rahman (Equilibrium: Jurnal Penelitian Pendidikan dan Ekonomi, 2020)
ABSTRACT This study aims to analizing the effect of organization culture and emotional intelligence of teachers on work ethic in vocational high school teacher at the west Jakarta. Research method is quantitative with multiple regression. Research methode is quantitative approach with regression analisys to proving the theory which is basis of the research hypotesys. Collecting data method is used the questionnaire with sample of 135 vocational teacher in public and private school of West Jakarta. Result of this research indicate that organizational culture and emotional intelligence significantly influencing the work ethic. Based on that result, vocational school management shoud be able to build an effective organizational culture and provide emotional spiritual questions (ESQ) training to the teacher in order to improve their work ethic. Keyword : Emotional_Intelligence, Organizational_Culture, Work_Ethic